Consumption of vegetables and their relation with ultra-processed foods in Brazil - Canella, Daniela Silva; Louzada, Maria Laura da Costa; Claro, Rafael Moreira; Costa, Janaina Calu; Bandoni, Daniel Henrique; Levy, Renata Bertazzi; Martins, Ana Paula Bortoletto (Revista de Saúde Pública, 2018)
OBJECTIVE: To characterize the household purchase and the individual consumption of vegetables in Brazil and to analyze their relation with the consumption of ultra-processed foods. METHODS: We have used data on the purchase of food for household consumption and individual consumption from the 2008–2009 Brazilian Household Budget Survey. The Brazilian Household Budget Survey studied the purchase of food of 55,970 households and the food consumption of 34,003 individuals aged 10 years and over. The foods of interest in this study were vegetables (excluding roots and tubers) and ultra-processed foods. We have described the amount of vegetables (grams) purchased and consumed by all Brazilians and according to the quintiles of caloric intake of ultra-processed food. To this end, we have calculated the crude and predicted values obtained by regression models adjusted for sociodemographic variables. We have analyzed the most commonly purchased types of vegetables (% in the total amount) and, in relation to individual food consumption, the variety of vegetables consumed (absolute number), the participation (%) of the types of culinary preparations based on vegetables, and the time of consumption. RESULTS: The adjusted mean household purchase of vegetables was 42.9 g/per capita/day. The adjusted mean individual consumption was 46.1 g. There was an inverse relation between household purchase and individual consumption of vegetables and ultra-processed foods. Ten types of vegetables account for more than 80% of the total amount usually purchased. The variety consumed was, on average, 1.08 type/per capita/day. Approximately 60% of the vegetables were eaten raw, and the amount consumed at lunch was twice that consumed at dinner; individuals with higher consumption of ultra-processed foods tended to consume even less vegetables at dinner. CONCLUSIONS: The consumption of vegetables in Brazil is insufficient, and this is worse among individuals with higher consumption of ultra-processed foods. The most frequent habit was to consume raw vegetables at lunch and with limited variety.